2017
DOI: 10.1038/mi.2016.104
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of TREM-1 ectodomain shedding and improved bacterial clearance by intranasal metalloproteinase inhibitors

Abstract: Triggering receptor expressed on myeloid cells-1 (TREM-1) is expressed on neutrophils and monocyte/macrophages and amplifies Toll-like receptor-mediated inflammation during infection. TREM-1 also exists in an antagonistic soluble form (sTREM-1) that has been used as a peripheral biomarker in sepsis, though the mechanisms of its release are not entirely clear. The requirement of TREM-1 in single microbial infections is controversial, with some studies showing a protective role and others a contribution to immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 51 publications
(50 reference statements)
1
33
2
Order By: Relevance
“…As the aMMP-8 (IFMA) levels increased, this seemed to result in an exponential increase in the TREM-1 levels verifying the association between the aMMP-8 PoC test and the TREM-1 levels. 23 Moreover, we found also a moderate positive correlation between the aMMP-8 (IFMA) and PGLYRP1 levels, but the functional form of this relationship was not as clear and strong as between aMMP-8 (IFMA) and TREM-1 levels in our cohort of adolescents. Although the approach in our study cannot directly reveal the cause-effect relationship 22 that one or several of the MMPs (MMP-1, MMP-2, MMP-3, MMP-8, and MMP-9) are responsible for this cleavage or shedding process of TREM-1.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…As the aMMP-8 (IFMA) levels increased, this seemed to result in an exponential increase in the TREM-1 levels verifying the association between the aMMP-8 PoC test and the TREM-1 levels. 23 Moreover, we found also a moderate positive correlation between the aMMP-8 (IFMA) and PGLYRP1 levels, but the functional form of this relationship was not as clear and strong as between aMMP-8 (IFMA) and TREM-1 levels in our cohort of adolescents. Although the approach in our study cannot directly reveal the cause-effect relationship 22 that one or several of the MMPs (MMP-1, MMP-2, MMP-3, MMP-8, and MMP-9) are responsible for this cleavage or shedding process of TREM-1.…”
Section: Discussioncontrasting
confidence: 50%
“…15 PGLYRP1 is known as an antibacterial protein against Gram-positive and Gram-negative bacteria. 22,23 Activated matrix metalloproteinase-8 (aMMP-8) is already known as one of the most validated periodontitis biomarkers. [17][18][19][20][21] There are studies that have identified proteolytic matrix metalloproteinases (MMPs) to be responsible for processing membrane bound TREM-1 to its soluble form.…”
Section: Introductionmentioning
confidence: 99%
“…shedding, to a soluble form (sTREM‐1) . The general perception is that proteolytic matrix metalloproteinases (MMPs) can process membrane‐bound TREM‐1 to sTREM‐1, allowing it to be a soluble candidate biomarker of inflammatory processes detected and reflected in biologic body fluids like serum or saliva . In this line, the authors demonstrated that periodontal pathogens can regulate the TREM‐1 signaling pathway in human monocytes and PMNs in a manner that amplifies proinflammatory responses .…”
mentioning
confidence: 99%
“…Presence of sTREM‐1 in systemic inflammatory diseases such as systemic sepsis, arthritis, and pulmonary disease, and in patients with kidney disease on hemodialysis is well documented, although recent evidence also exists for the association of salivary and serum TREM‐1 with the local oral inflammatory disease periodontitis …”
mentioning
confidence: 99%
“…However, recently, the origin of sTREM-1 has been established in mice, demonstrating that membrane TREM-1 contains a matrix metalloproteinase 9 (MMP-9) cleavage site and that the inhibition of MMP-9 reduces the amount of sTREM-1 6. Similarly, human TREM-1 also contains a theoretical MMP-9 cleavage site,7 raising the hypothesis that sTREM-1 is cleaved off the cell surface by MMPs 8.…”
mentioning
confidence: 99%